Developing an Extreme Multidimensional Poverty Indicator in Indonesia: A Positive-Theoretical Inquiry and an Integrated Shariah Perspective - Agung Pardini (Journal of Economicate Studies, 2026)
This study develops a comprehensive theoretical framework for measuring extreme multidimensional poverty in Indonesia, arguing that conventional monetary indicators such as US$2.15 and US$3.00 PPP are inadequate to capture the full scope of deprivation. By integrating Amartya Sen’s capability approach, basic-needs theory, human rights–based development, and principles of distributive justice in Islamic economics, the research conceptualizes extreme poverty as a multidimensional condition involving economic hardship, limited access to essential services, social vulnerability, and restricted individual agency. Using qualitative literature analysis, the study proposes an indicator framework encompassing health, education, housing, energy access, economic security, and spiritual capability aligned with maqāṣid al-sharī‘ah. The findings highlight the need for poverty measurement systems that combine economic, moral, and institutional dimensions, offering important implications for improving poverty policy, targeting mechanisms, and the integration of Islamic economic instruments in Indonesia, while also laying the groundwork for future empirical validation and policy experimentation.